2016
DOI: 10.1007/s00038-015-0784-6
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use among US adolescents: secondhand smoke at home matters

Abstract: The association between smoking habits of the family and e-cigarette use was mediated through SHS exposure. The promotion of smoke-free home rules may help prevent the uptake of e-cigarettes among teenagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
4
10
0
Order By: Relevance
“…While SHS exposure alone was not significant, it is possible the association is mediated through living with a smoker6 or lack of home tobacco ban, which were controlled for in our findings. Concordant with previous research,17 SHS exposure increased the likelihood of EVP susceptibility. We further found that SHV exposure had an even stronger association with EVP susceptibility.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While SHS exposure alone was not significant, it is possible the association is mediated through living with a smoker6 or lack of home tobacco ban, which were controlled for in our findings. Concordant with previous research,17 SHS exposure increased the likelihood of EVP susceptibility. We further found that SHV exposure had an even stronger association with EVP susceptibility.…”
Section: Discussionsupporting
confidence: 90%
“…Current research suggests SHS exposure may increase susceptibility to cigarette smoking13 16 32 33 and e-cigarette use,17 and SHS exposure may mediate the association between parents smoking and students smoking 34. To our knowledge, no studies have evaluated the relationship between SHV exposure and tobacco susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hundred and fifty articles 153,192194,197,203,239,265,271,304,323326,329,332,333,335339,341344,346,348,350,351,353362,365,367369,372,374376,378381,384,388,390,393396,404406,408,414416,418,420422,425,426,432,434,436,440,441,444450,453456,459462,465,468,472,475,476,478,488,489,491,494,496498,500,502,504,506646 have been published on vaping patterns.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Therefore, the growing importance of electronic cigarettes needs to be considered in future measures designed for the protection of non-smokers. Electronic cigarettes and SHS exposure may be a mediator between parental smoking and smoking initiation among children [37, 38]. The study indicates that the factors associated with SHS exposure differ only slightly after they are stratified in terms of the type of tobacco product leading to SHS exposure.…”
Section: Discussionmentioning
confidence: 99%